2021
DOI: 10.1136/bmjsem-2021-001199
|View full text |Cite
|
Sign up to set email alerts
|

Cam morphology is associated with MRI-defined cartilage defects and labral tears: a case–control study of 237 young adult football players with and without hip and groin pain

Abstract: ObjectiveFootball players are at risk of developing hip osteoarthritis (OA). Cam morphology (present in almost two of every three football players) may explain this heightened risk, but there is limited research on its role in hip OA development in younger athletes. Knowledge of this relationship will advance our understanding of the aetiology of hip OA in football players. We aimed to study the relationship between cam morphology size and MRI-defined cartilage defects and labral tears, and if this relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…Our findings are consistent with previous reports of a dose-response relationship between cam morphology and physical findings, where those with larger cam morphology had worse chondrolabral pathology 8,9 and restricted ROM. 11 It is unclear why football players with larger cam morphology reported worse perceived impairment to physical function than those with smaller cam morphology, warranting future investigation of the relationship between cam morphology size and hip joint biomechanics during sporting tasks.…”
Section: Perspectivesupporting
confidence: 93%
See 3 more Smart Citations
“…Our findings are consistent with previous reports of a dose-response relationship between cam morphology and physical findings, where those with larger cam morphology had worse chondrolabral pathology 8,9 and restricted ROM. 11 It is unclear why football players with larger cam morphology reported worse perceived impairment to physical function than those with smaller cam morphology, warranting future investigation of the relationship between cam morphology size and hip joint biomechanics during sporting tasks.…”
Section: Perspectivesupporting
confidence: 93%
“…Maximum alpha angle measurements are frequently observed at the anterosuperior region of the femoral head-neck junction, 4,[15][16][17] where larger and more anterior cam morphology has been found to impinge the acetabulum at smaller degrees of hip flexion. 27 While mechanical impingement between the femoral neck and acetabulum may increase hip joint stresses, 28 restrict ROM, 11,29 and cause chondrolabral pathology, 8,9 the effect of cam morphology on reported burden has been less certain. Cam morphology presence 13,14 and size 2,30,31 have been unrelated to PROM scores in various symptomatic populations, including those undergoing hip arthroscopy, 30,31 adults with self-reported hip OA, 13 and football players with hip/groin pain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent MRI study looking at young football players (mean age 26 years) found an association between cam morphology size and risk of chondrolabral damage. Interestingly, the relationship was similar in symptomatic and asymptomatic patients [ 40 ]. With chondrolabral damage being a continuum, it is likely too early for participants in this study to show any important cartilage damage that may cause hip pain [ 39 ].…”
Section: Discussionmentioning
confidence: 99%